Young consumers' motives for using SMS and perceptions towards SMS advertising - Phau, Ian; Teah, Min (University of Western Sydney, 2008)
The purpose of this study is to examine young consumers' motives for using SMS, their SMS usage frequency, and their attitudes towards SMS advertising. Factor analysis on the motives for using SMS revealed seven factors, namely convenience, social involvement, enjoyment, escape, personal communication, economical reasons, and public expression. The findings show that convenience and economical reasons influence SMS usage frequency. Social involvement influences attitudes towards SMS advertising. Managerial implications and limitations are also presented.